2018
DOI: 10.1103/physreva.98.032326
|View full text |Cite
|
Sign up to set email alerts
|

Universal and distortion-free entanglement concentration of multiqubit quantum states in the W class

Abstract: We propose a multipartite extension of Matsumoto and Hayashi's distortion-free entanglement concentration protocol, which takes n copies of a general multipartite state and, via local measurements, produces a maximally-entangled multipartite state between local spaces of dimensions ∼ 2 nE i , where Ei are the local entropies of the input state. However, the extended protocol is generally not universal in the sense that for the same measurement outcomes, the output state will still depend on the input state. Ou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…, and Gram-Schmidt orthogonalization have been discussed in the literature under the name of Schur-Weyl states [40,[64][65][66], or Gelfand-Tsetlin states [67][68][69][70]. Although not necessary for the block-diagonalization of the Hamiltonian, an illustration of the explicit form of the symmetrized states in terms of the PBEs might be useful for the reader.…”
Section: Schur-weyl Basismentioning
confidence: 99%
“…, and Gram-Schmidt orthogonalization have been discussed in the literature under the name of Schur-Weyl states [40,[64][65][66], or Gelfand-Tsetlin states [67][68][69][70]. Although not necessary for the block-diagonalization of the Hamiltonian, an illustration of the explicit form of the symmetrized states in terms of the PBEs might be useful for the reader.…”
Section: Schur-weyl Basismentioning
confidence: 99%
“…In [24] a family of entanglement measures have been constructed based on the rate function corresponding to the standard representation of products of unitary groups. While studying a tripartite extension of the Matsumoto-Hayashi universal distortion-free entanglement concentration protocol [18], Botero and Mejía [5] found formulas for the probabilities induced by the isotypic decomposition or tensor powers of the U (2) n -representation C 2 ⊗n when the state is in the W class.…”
Section: Introductionmentioning
confidence: 99%
“…However, the channel noise will induce decoherence and degrade the entanglement between the quantum systems. Entanglement concentration [11][12][13][14][15][16][17][18][19][20][21][22][23] is an operation which converts a partially entangled state to a more or maximally entangled state. Since the first entanglement concentration protocol (ECP), the well known Schmidt projection, was proposed by Bennett et al [11], its realization on the various physical systems has been reported.…”
Section: Introductionmentioning
confidence: 99%